EVALUATION OF ENTREPRENEURSHIP DEVELOPMENT OF PRIVATE PRISONERS THROUGH INDUSTRIAL ACTIVITIES PROGRAM AT WOMEN'S PENALTY INSTITUTION IN SEMARANG USING THE DISCREPANCY EVALUATION MODEL (DEM) METHOD - Dewi Ambarwati; Taufiq Amir (Jurnal Scientia, 2023)
The purpose of this study was to find out and analyze how the evaluation of the implementation of entrepreneurship development through the Industrial Activity Program at the Semarang Women's Prison. This research method uses a qualitative approach. This research data collection method using documentation, interviews and observations. Key informants in this study are the Head of Prisons, prison officers, working prisoners, NGOs who teach, community, businessmen/partners. The data analysis technique used the Discrepancy Evaluation Model (DEM) method. The results showed that although there are still discrepancies in 5 (five) sub-focus, namely the legal basis, cooperation network, implementation process, results and benefits, but the Semarang Women's Prison in implementing the industrial activity program, it has been implemented in in accordance with the SOP approved by the Director General of Corrections, even made additional SOPs to support the program in question. Human resources in charge of industrial managers in prisons are very less than ideal needs, both in terms of competence and quantity. Even so, industrial activities in prisons continue to run well. This is inseparable from the leadership characteristics possessed by the Semarang Women's Headquarters. Although organizational commitment is felt to be not optimal for the implementation of the program. However, in reality, until now the industrial activity program that must be implemented at the Semarang Women's Prison has produced quality products / services.